Mental health and victimization: an exploratory study in prisons of Cape Verde - Dias, Ana Rita Conde (2022)
Background: There is insufficient information available regarding the psychopathological characteristics of the inmate population in low-middle-income countries as Cape Verde. Objective: This study aimed to determine the prevalence of mental disorders in a sample of Cape Verdean inmates and explore its’ relation with victimization in the prison context Participants and methods: This cross-sectional study was carried out in 5 prisons of Cape Verde. 402 subjects were included in stratified convenience sample and assessed with Brief Symptom Inventory (BSI) and a sociodemographic questionnaire. Data was analyzed using SPSS 25 software applying descriptive and inferential statistical measures. Results: Inmate ́s mean age was 31, 16 years, mainly men (96%), single (87,6%) from Cape Verde (90,8%) with a basic level of education. 62.9% reported substance use problems. According to the psychopathological dimensions included in BSI, paranoid ideation, obsessive-compulsive and depressive symptoms stand out either in the sample or in the 2 sub-samples. Symptomatology was significantly higher among victims namely in interpersonal sensitivity), anxiety and hostility. The increasing reoccurrence of victimization in the past 12 months is associated with an increase in the severity of symptoms. Conclusion: Victimization and mental health problems should be identified as early as possible to enable joint and combined intervention, given the negative impact of psychopathological manifestations on the reintegration of prisoners in society affecting the reintegration of prisoners into society.